Detailed Chemistry Studies of 225Actinium Labeled Radiopharmaceuticals - Eryilmaz, Kurtulus; Kilbas, Benan (Current Radiopharmaceuticals, 2022)
Background: The synthesis of 225Actinium derivatives was afforded by using PSMA- 617, DOTATATE peptides, and EDTMP ligand. Detailed experiments, quality control (QC), and stability studies were also well described. The radiolabelling reactions were performed in mild conditions with desirable radiochemical yields and high radiochemical purities. Methods: PSMA-617, DOTATATE were radiolabelled with 225Actinium in 0.1 M HCl in the presence of ascorbate buffer solution and passed through the C-18 light cartridge for purification and the product was eluted by ethanol-water solution. EDTMP was also radiolabelled with 225Actinium without using any stabilizer and purification step. All products were well analyzed by R-TLC and R-HPLC. The stability of those compounds was also studied within the validity period of time. Results: 225Ac-DOTATATE and 225Ac-PSMA-617 were obtained at the same condition. The radiochemical yield of 225Ac-DOTATATE was less than225Ac-PSMA 617. The stability experiments indicating decay daughters of 225Actinium appeared after T0 +1 h due to the recoil effect radiolysis. On the other hand, 225Ac-EDTMP was more stable than DOTA-peptide radiolabelled compounds. 225Ac-EDTMP was produced with more than 95% radiochemical yield and 99% radiochemical purity. Conclusion: A detailed chemistry study was presented for the synthesis of 225Actinium derivatives in mild conditions with absolute radiochemical purities and high yields. The experimental results showed that 225Ac-EDTMP could be a suitable radiopharmaceutical alternative for bone metastases arising from primer tumors as a cocktail therapy.
Keywords: QC